A construção da subjetividade na obra de Antonio Tabucchi: Afirma Pereira - Ferreira, José Ribamar (2017)
This research aims to investigate the construction of subjectivity in Antonio Tabucchi’s novel Afirma Pereira, as well as the writing resources used by the author in the making of a certain type of subject amidst the existential uncertainties in the end of the 1930s, in the context of the Salazar regime. The analytical bias of this study assumes that Antonio Tabucchi proposes, throughout the novel, literature as a form of political resistance, and also the construction of one’s subjectivity in the search of self-affirmation in the middle of Portugal’s totalitarian ideology. Moreover, this research demystifies the ideological discourses that have contributed to the deconstruction of the subjectivity of the subject, such as alienation, self-restraint, and solitude. We furthermore identify in Afirma Pereira the identity crisis of the modern man, who was trapped in his “hegemonic self” and, therefore, alienates himself. Finally, we problematize the appearance of existential problems experienced by the character Pereira in that very troubled period of the history of Portugal, such as anxiety, melancholy, fear, insecurity, solitude, and uncertainties, among other symptoms of that country’s social-historical situation during the Salazarism. Concerning the construction of the subjectivity, the research is based on the reflections of Jean-Paul Sartre, Kierkegaard, Fernando Pessoa, Octavio Paz, and other authors. Through this research, we hope to communicate to the reader that it is indeed possible, from the enunciative voice of Afirma Pereira’s testimony, to elucidate and demystify ideological discourses and ethnocentric paradigms that prevail over people’s consciousness and prevent them from asserting themselves in the world